2018
DOI: 10.1017/s0373463318000103
|View full text |Cite
|
Sign up to set email alerts
|

Orbit and Positioning Accuracy for New Generation Beidou Satellites during the Earth Eclipsing Period

Abstract: The Beidou System (BDS) started functioning at the end of 2012. The Yaw-Steering (YS) attitude mode for Inclined Geosynchronous Orbit (IGSO) and Medium Earth Orbit (MEO) satellites in BDS ensures that the solar panels face the Sun. The orbit radial accuracies for IGSO/MEO satellites are 0·5 m and the User Equivalent Range Errors (UERE) are 1·5 m in YS mode. BDS-2 satellites adopt Orbit-Normal (ON) mode to meet the power supply and thermal control requirements of the satellite during deep Earth eclipse periods.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…For BDS-2 IGSO and MEO satellites, the Yaw-Steering (YS) and ON modes are adopted. The transformation from YS to ON occurs when the absolute value of β angle is less than 4° and the absolute value of yaw angle ( ψ angle) is no greater than 5° (Li et al, 2018), while the conditions for switching from ON to YS are |β| > 4 • and |ψ| < 5 • . They present the yaw angles during the attitude switch period from the telemetry data for C08, C11 and C12 satellites, and the sudden rump-up and rump-down jumps instead of smooth switch can be clearly observed at the attitude switch points.…”
Section: Yaw Attitudementioning
confidence: 99%
See 1 more Smart Citation
“…For BDS-2 IGSO and MEO satellites, the Yaw-Steering (YS) and ON modes are adopted. The transformation from YS to ON occurs when the absolute value of β angle is less than 4° and the absolute value of yaw angle ( ψ angle) is no greater than 5° (Li et al, 2018), while the conditions for switching from ON to YS are |β| > 4 • and |ψ| < 5 • . They present the yaw angles during the attitude switch period from the telemetry data for C08, C11 and C12 satellites, and the sudden rump-up and rump-down jumps instead of smooth switch can be clearly observed at the attitude switch points.…”
Section: Yaw Attitudementioning
confidence: 99%
“…With the Revise Kinematic Precise Point Positioning (RKPPP) approach proposed by Dilssner et al (2011), the yaw angles were estimated with ground L-band measurements Dai et al, 2015). Almost the same conditions as Li et al (2018) are derived by Dai et al (2015). However, by assuming that the attitude mode will switch when the yaw angle is closest to the required orientation, Guo et al (2017) derived the conditions for yaw attitude switch when µ = 90 • and |β| closest to 4°, where µ is the orbital angle.…”
Section: Yaw Attitudementioning
confidence: 99%
“…For the BDS-2 satellite, studies have shown that its orbit determination accuracy will decrease significantly during the eclipse period [20], but there are few studies analyzing the orbit prediction accuracy of the BDS-3 satellite during the eclipse season. Therefore, in the following section, this study explores the orbit prediction accuracy of the BDS-3 satellite during the eclipse season.…”
Section: Orbit Prediction Accuracy When Satellites Are During and Out...mentioning
confidence: 99%
“…The reason may be due to the advanced attitude control mode of the BDS-3 satellites. In addition to the yaw-steering (YS) mode, the BDS-3 MEO/IGSO satellites adopt the continuous yaw steering (CYS) attitude mode in eclipse seasons [20]. The CYS mode not only meets the requirements of the power supply and thermal control of the BDS-3 MEO/IGSO satellites but also avoids rapid yaw slews near the sun-spacecraft-Earth geometries.…”
Section: Orbit Prediction Accuracy When Satellites Are During and Out...mentioning
confidence: 99%
See 1 more Smart Citation